English for Computer Science and Information Technologies - Lazareva, O.; Berkutova, T.; Vrakina, V.; Goncharenko, T.; Grashchenkova, V.; Dyomochka, L.; Kovtun, O.; Salamatina, A.; Vnukova, K. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The textbook consists of 8 units on specific areas of information technology: Artificial Intelligence, Big Data, Web Design, etc. Each unit contains texts, video, audio materials aimed at expanding vocabulary, developing communicative skills and the ability to work independently and in a team. All texts, audio and video materials are selected from authentic professional or popular science sources. It is intended for students of computer and information technology faculties, full-time and extramural study.

Навчальний посібник складається з 8 розділів за окремими галузями інформаційних технологій: Artificial Intelligence, Big Data, Web Design, тощо. Кожен розділ містить текстові, відео або аудіо матеріали на розширення словникового запасу, розвиток комунікативних навичок, вміння працювати самостійно та в команді. Всі тексти, аудіо та відеоматеріали відібрані з автентичних професійних або науково-популярних джерел. Призначено для студентів факультетів комп'ютерних та інформаційних технологій, денної та заочної форм навчання.
Keywords: textbook; computer science; information technologies; web design; cyber security; IT jobs